Users’ Satisfaction towards Justice Channel Website of the Office of Justice Affairs - Angthararak, Nawaporn; Gluntapura, Oranan (Journal of Social Development and Management Strategy, 2023)
The objectives of this study were as follows: 1) to study the level of users’ satisfaction towards Justice Channel website of the Office of Justice Affairs, 2) to compare the users’ satisfaction towards Justice Channel website of the Office of Justice Affairs, classified by personal factors and media exposure behavior. This study was quantitative research. The purposive sampling was used. Data were collected by using an online survey from 400 persons who visited the Justice Channel website. The results of this study were found that the users’ satisfaction towards Justice Channel website of the Office of Justice Affairs both overall and each aspect were at a high level The considering each aspect ordered from the highest to the least, that was design aspect, content aspect and usability aspect. It was also found that ages, occupations, and incomes had effects on the users’ satisfaction towards Justice Channel website of the Office of Justice Affairs at the statistical significance of p < 0.05. As for the media exposure behavior, it was found that the website users with different frequency of media exposure, media formats selected on website, and used devices had different level of satisfaction towards the Justice Channel website of the Office of Justice Affairs at the statistical significance of p < 0.05. The results of the study will be used to further develop and improve the Justice Channel website.